Bkaʼ brgyad Bde gśegs ʼdus paʼi chos skor : a reproduction of a manuscript collection of texts from the revelations of Mṅaʼ-bdag Ñaṅ-ral Ñi-ma-ʼod-zer - Ñaṅ-ral Ñi-ma-ʼod-zer, 1124-1192 (Damchoe Sangpo, 1977)
Ritual practices of a Nyingmapa cycle of rediscovered teachings; includes biographical accounts of the early gurus of the transmission.